(3CRgGQ GdQjGV aj CNHGQ GdbGVi YjGVs - (3CMeO Hf eMeO Hf CMeO Hf jMji, CHh GdYHGS GdebQj GdJdeSGfj,J (B1041 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CYdi eQGJH GdYdeGA GdCYdGe hHYO hCSQi ef GdehGgH CSfGgG hef GdYhGbH MSHfG s
(3BNQgG (B:s
(3hcPdc BjI GdeHGgdI PcQgG SHMGfg Hbhdg (B" (3Ef gPG dge GdbUU GdMb (B" (3GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJGQjNs